Trophic and non-trophic interactions in binary links affect carbon flow in the soil micro-food web. (August 2019) - Richter, Andreas; Kern, Toni; Wolf, Sebastian; Struck, Ulrich; Ruess, Liliane
Abstract: Soil organisms constitute multitrophic food webs, which are important determinants for nutrient and carbon flow through terrestrial systems. However, these complex interactions are not well understood, particular in the most cryptic compartment – the link between microorganisms and microfauna. The present study investigates binary trophic links between microbial prey and nematodes in a controlled semi-natural soil environment. A microcosm system with circulating airflow was filled with γ-irradiated arable soil (Luvisol), inoculated with 13 C labelled microbial diet and nematode grazers, and incubated for 72 h. Signatures of 13 C and CO2 evolved from microcosms, soil phospholipid fatty acids and nematode densities were determined. Except for the model nematode Caenorhabditis elegans, all organisms joint in the 12 different investigated binary links represent dominant taxa at the arable field site. Studied were the fungal grazers Aphelenchoides saprophilus and Aphelenchus sp. in combination with the fungi Chaetomium globosum, Aspergillus terreus or Cryptococcus terreus as well as the bacterial grazers C. elegans and Acrobeloides buetschlii in combination with the bacteria Pseudomonas putida, Kitasatospora sp. or Sphingomonas trueperi . The results assigned trophic and non-trophic interactions and considerable variation between binary links. The biomass decline of S. trueperi in presence of C. elegans as well as the increased release of 13 C in links of C. globosum and A. terreus with Aphelenchus sp. and S. trueperi with A. buetschlii assign nematode grazing and thus a classical predator-prey system. Such direct trophic interactions can induce distinct C fluxes within a binary link as assigned by the increased density (i.e. biomass) of C. elegans when feeding on S. trueperi . In contrast, the numbers of Aphelenchus sp. declined when feeding on A. terreus, and thus reduced C flow to the next trophic level. Grazing can also foster C allocation in microbial biomass via compensatory growth, as indicated e.g. for the link of Aphelenchus sp. with the fungi C. globosum and A. terreus . While these diverse responses to grazing were to be expected, the use of CO2 and 13 C measurements further revealed that non-trophic interactions shape C flux in a binary link, particularly in the bacterial channel. Besides the fungal link of C. terreus with Aphelenchus sp., non-trophic interactions were obvious for the bacterial links Kitasatospora sp. with C. elegans or A. buetschlii, and P. putida with A. buetschlii . The presence of nematodes caused a reduction in respiration (evolved CO2 ), thus a decline in microbial activity. The formation of chemical and/or morphological defense is likely a reason for that reduced prey activity. For further studies the inclusion of such non-trophic interactions is necessary to achieve realistic models for C flow through soil food webs. Highlights: Microbial traits cause variation in palatability for nematode grazers. Predator-prey interactions of nematodes within a functional guild differ. Impact of non-trophic interactions on C flux depends on the specific binary link.